PELAKSANAAN PROGRAM TAHFIDZ AL-QUR’AN DALAM MEMBENTUK KARAKTER RELIGIUS SANTRI PADA PONDOK PESANTREN DDI (DARUD DA’WAH WAL-IRSYAD) MATTOANGING KABUPATEN BANTAENG - ., Arifuddin; Usman, Syahruddin; Muzakkir (Inspiratif Pendidikan, 2022)
This study discusses the implementation of the Tahfidz Al-Qur’a>n program in shaping the religious character of students at the DDI Islamic Boarding School (Daarud Da’wah Wal-Irsyad) Mattoanging, Bantaeng Regency with the aim of: 1) describing the Tahfidz Al-Qur’a> program. n at the DDI Mattoanging Islamic Boarding School, Bantaeng Regency. 2) describe the religious character of the Santri at the DDI Mattoanging Islamic Boarding School in Bantaeng Regency. 3) describe the implementation of the Tahfidz Al-Qur’a>n program in shaping the religious character of students at the DDI Mattoanging Islamic Boarding School, Bantaeng Regency. The results of this study indicate that: 1) the Tahfidz Al-Qur’a>n program is a program of mentoring and fostering tahfidz Al-Qur’a>n which is always carried out as a forum in creating a generation of memorizing Al-Qur’a>n through takhassus memorization. and non takhassus. The implementation of tahfidz with takhassus criteria is 15 people with the highest memorization of 9 juz and the lowest 1 juz and non takhassus totaling 19 people with the highest memorization of 1 juz and the lowest half juz. tahsin Al-Qur’a>n; b bilghaib (memorizing) or Ziadah (adding memorization); c) muraja’ah/takrir and d) simaan; 2) Religious character is considered very important and is always taught, preserved and practiced for santri and female students which includes discipline, honesty, courtesy, sincerity and istiqomah, patient, humble / humble, obedient to worship and responsible; 3) the implementation of the Tahfidz Al-Qur’an program in shaping the religious character of students is carried out in several ways, namely conveying the traditions of the Prophet about adab, advice, conducting supervision and attention, giving punishment and keeping away from electronic access and the like.